(untitled) (Research, Society and Development, 2022)
Human sexuality has gone through several conceptions, reflections and problematizations during the history of humanity, taking into account time, factors such as: science, religion and culture. These conceptions about sexuality mark history with particular definitions. Thus, analyzing all the political, cultural and social issues of the LGBTQIAP+ community, this study aims to analyze, within the scientific scenario, the impacts of sexuality, gender identity and interference in mental health. This is an integrative review of scientific literature. A search was carried out for articles with available abstracts that were related to sexuality, gender identity and that refer to the implication in the subject’s mental health. In the search for articles, "sexuality", "gender identity" and "mental health" were used as descriptors and the data was crossed. The search for articles was carried out in the databases of Latin American and Caribbean Literature in Sciences of Health (LILACS) and Scientific Electronic Library Online (SCIELO).The inclusion criteria defined for the selection of articles were: articles with abstracts and full texts available for analysis; articles related to sexuality, gender identity with reflections on mental health; published in Portuguese, English or Spanish, in full and indexed in the aforementioned databases from 2017 to 2021. Ten studies were analyzed for this review, in which it was possible to identify the problems related to the mental health of the LGBTQIAP+ population.